Application of Internet of Things (IoT) Technology to KWT “Sido Makmur” Oyster Mushroom Cultivation - Widyasmoro Widyasmoro; Taufiq Hidayat; Tony K Hariadi; Norazhar Bin Mohamed Sepet; Wee Eng Soon (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Ngaran Hamlet, an area in Gilangharjo Village, Pandak District, Bantul Regency, DIY, has a Women Farmers Group (KWT), "Sido Makmur," which is engaged in oyster mushroom cultivation. One of the challenges KWT "Sido Makmur" faces is the fluctuation and instability of oyster mushroom production due to environmental conditions around the mushroom barn, which are not always ideal. To overcome this, the Community Service Team from Universitas Muhammadiyah Yogyakarta (UMY), in collaboration with Singapore Polytechnic (SP), carried out Community Service activities under the Community Partnership (PKM) scheme. This service aims to assist KWT "Sido Makmur" in facing the challenges of oyster mushroom production by designing and implementing Appropriate Technology in the form of a temperature and humidity monitoring system in mushroom barns based on the Internet of Things (IoT). The service team's programs and activities include planning, designing, implementing, testing, and analyzing the IoT technology-based mushroom monitoring system for temperature and humidity. This system allows oyster mushroom farmers in Ngaran Hamlet to monitor the condition of the mushroom coop in real-time and remotely via the IoT platform to increase the productivity of oyster mushrooms optimally. The results of the implementation and testing of the system show that the monitoring tool for temperature and humidity in the IoT-based mushroom barn has been proven to function properly in accordance with the design planning and expectations of oyster mushroom farmers in Ngaran Hamlet.